Affordable “Do-It -Yourself” learning tools for learning “Human Reproductive System” / Siti Hajar Md.Jani, Dr. Jamali Wagiman and Tuan Sarifah Aini Syed Ahmad - Md. Jani, Siti Hajar; Wagiman, Jamali; Syed Ahmad, Tuan Sarifah Aini (Academy of Language Studies, Universiti Teknologi MARA Negeri Sembilan Branch, Rembau Campus, 2023)
In today's fast-paced world, acquiring new skills and knowledge are essential for personal growth and professional development. However, the cost of education and learning aids can often deter individuals from pursuing their educational goals. Fortunately, there are numerous low-cost and highly efficient learning aids available that can empower learners without burdening their wallets. In this article, we will provide an illustration of one of best and most reasonably priced learning tools that will boost learners’ performance in their sixth-year science course at the primary school level on the human reproductive system. For this science topic, we choose to create a "Do-It -Yourself" educational projects or known as DIY.